1999
DOI: 10.1002/(sici)1521-4141(199906)29:06<2026::aid-immu2026>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of antibody responses to new B cell epitopes indicates vaccination character of allergen immunotherapy

Abstract: Whether the modulation of antibody responses can contribute to the improvement of clinical symptoms in patients receiving allergen immunotherapy represents a controversial issue. We have used purified [seven recombinant (r) and one natural] timothy grasspollen allergens as well as recombinant B cell epitope‐containing fragments of the major timothy grass pollen allergen, Phl p 1, to investigate humoral immune responses in eight allergic patients receiving grass pollen‐specific immunotherapy. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 53 publications
4
75
0
1
Order By: Relevance
“…This suggests a functional role of IgG4 in inhibition of IgE-FAB, which may be due to changes in their specificity and/or affinity. Another role of allergen-specific IgG4 antibodies induced by immunotherapy is their ability to block allergen-induced IgE-dependent histamine release by basophils confirming the functional blocking activity of these antibodies (Ball et al, 1999;Lambin et al, 1993).…”
Section: Discussionmentioning
confidence: 74%
“…This suggests a functional role of IgG4 in inhibition of IgE-FAB, which may be due to changes in their specificity and/or affinity. Another role of allergen-specific IgG4 antibodies induced by immunotherapy is their ability to block allergen-induced IgE-dependent histamine release by basophils confirming the functional blocking activity of these antibodies (Ball et al, 1999;Lambin et al, 1993).…”
Section: Discussionmentioning
confidence: 74%
“…(Table 1). Injection immunotherapy with natural allergen extracts is known to induce mainly Th2-like immune responses (i.e., IgG4) (22,23). However, the allergy vaccines that we developed led to a change of the allergic immune response toward a Th1 phenotype, as shown by the induction of IgG2 Abs in both actively treated groups (Table 1).…”
Section: Methodsmentioning
confidence: 94%
“…Granulocytes from birch pollen-allergic donors were isolated by dextran sedimentation from heparinized blood samples (21). Different concentrations (0.001, 0.01, 0.1, 1, and 10 g͞ml) of rBet v 1, rAln g 1, and (for control purposes) an immunologically unrelated allergen (i.e., timothy grass pollen allergen, Phl p 1) or anti-IgE Abs were incubated with sera obtained before and after treatment and then exposed to the granulocyte preparation (22)(23)(24). Histamine released into culture supernatants was measured by RIA (Immunotech, Marseille, France).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that allergen-specific IgG Abs can inhibit the IgE-mediated release of biological mediators from effector cells and thus may prevent immediate symptoms (37,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of patients by component-resolved diagnosis will allow component-resolved immunotherapy with the disease-eliciting allergen and thus prevent de novo sensitization against other components present in natural allergen-extracts (15,53). As rBet v 1 fragments exhibited a Ͼ100-fold reduced allergenic activity, we expect fewer side effects and think that higher doses can be administered.…”
Section: Discussionmentioning
confidence: 99%